- Gentamicin Polymethyl Methacrylate Beads and Chains (Septopal): Pharmacokinetic, bacteriological, biological and biomechanical aspects - Barquet, Antonio (Cirugía del Uruguay, 1982)
Gentamycin-PMMA pearls release the antibiotic locally by diffusion in high quantities and for long periods of time. Pharmacokinetic studies in vivo show; after the implantation of these chains and pearls; the neglectable urinary and serum diffusion of gentamycin, and the high concentrations at the focus. These con e en trations surpass the minimal inhibítory concentration for the big maiority of germs that usually cause pyogenic infection of bone and soft tissue. Its biological and biomechanical properties are considered, along with the pharmacokinetic and bacteriologjcal findings. All these properties and findings justífy its widespread use supplementing necrectomy, in the therapeutical schemes.